Republic of Mozambique: Final Report General and Provincial Assembly Elections - European Union Election Observation Missionn (European Union Election Observation Mission, 2019)
On 15 October, Mozambicans elected the president, members of the Assembly of the Republic, members of the 10 provincial assemblies, and 10 provincial governors. Although there was a considerable number of participants, including recently registered political parties, the electoral process was dominated by the three main parties: the ruling Mozambican Liberation Front (FRELIMO), the main opposition Mozambican National Resistance (RENAMO), and the Mozambican Democratic Movement (MDM)
Keywords: G - Mozambique / Moçambique; L - english / inglês; electoral geography / geografia eleitoral

Democratization of Health Services: Dynamics of Administrative Resistances (N'weti - comunicação para saúde, 2019)
This policy brief, apart from describing the dilemmas of the democratization process of health services it, aims to analyze its implications on the dynamics of social accountability in the health sector and, finally, to inform on possible ways for a more coherent democratization, considering the normative discourses
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização; decentralization / descentralização; health / saúde

Scenarios for Violence in the Resource-rich Cabo Delgado Province - Devermont, Judd; Columbo, Emilia (Center for Strategic and International Studies (CSIS), 2019)
The government of Mozambique has a rapidly shrinking window within which to implement a more comprehensive and effective strategy to weaken the Ahlu Sunna wa Jama (ASWJ) insurgents in Cabo Delgado and prevent the group from becoming an entrenched, long-term security problem. This report projects that the security situation in Cabo Delgado will most likely deteriorate during the next 18 months if the ASWJ insurgency continues to recruit new fighters and maintains a high frequency of attacks, as they have done since October 2017. Another key destabilizing factor is a government response that prioritizes military action over community development programs as its primary line of effort against the group. The government’s heavy-handed counterinsurgency approach risks further alienating the local population, driving them to lend active and passive aid to the militants. While the complete pacification of the group is unlikely during the next 18 months, a concerted whole-of-government approach would help undercut the group’s momentum. This includes outreach to the local community, programs, and policies designed to address specific grievances, and the use of targeted military operations. Maputo’s partners in the international community and private sector also have an important role to play. They can leverage their political influence and financial resources to press the Mozambican government to shift its current approach toward one that addresses the underlying grievances driving the insurgency. In doing so, Maputo and its partners have a better opportunity to not only undercut the present violence but potentially prevent future armed groups from emerging.
Keywords: G - Mozambique / Moçambique; GP - Cabo Delgado; L - english / inglês; security / segurança; ⛔ No DOI found

The Genesis of Insurgency in Northern Mozambique - Matsinhe, David M.; Valoi, Estacio (Institute for Security Studies (ISS), 2019)
Insurgents have attacked towns and villages in Cabo Delgado, the poorest province in Mozambique. The government has responded by sending in the military to stamp out the assailants, using ‘whatever it takes’, amid suspicions that foreign fighters from Tanzania have radicalised local youth who are behind the violence. Other measures to counter the violence include an extra-judicial state of emergency and the suppression of information.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; extractive industries / indústrias extractivas; youth / juventude

Radicalização Islâmica no Norte de Moçambique: O Caso de Mocímboa da Praia - Habibe, Saide; Forquilha, Salvador; Pereira, João (Instituto de Estudos Sociais e Económicos (IESE), 2019)
Este artigo analisa o fenómeno da radicalização islâmica no Norte de Moçambique, explorando a complexidade das dinâmicas não só na origem do grupo dos Al-Shabaab como também na estrutura do próprio conflito e violência em Cabo Delgado. Os autores consideram que o fenómeno exige uma pesquisa multidisciplinar aprofundada que tome em conta uma multiplicidade de factores de ordem histórica, social, política, económica e religiosa. Acesso à versão inglesa aqui.
Keywords: *indexed; *snowball; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Mocímboa da Praia; GP - Cabo Delgado; L - portuguese / português; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; poverty / pobreza; youth / juventude

Towards Social, Economic and Inclusive Policies for People with Disability in Mozambique - Khadiagala, Gilbert M.; Manhique, Jorge R. (WFD - Moçambique, 2019)
The inclusion of persons with disabilities is an essential element of a strong democracy and a just society. Persons with disabilities (PWDs) being included means that they have a full and equal opportunity to participate in society and in political decision-making processes, to develop their capacities, and to contribute to national progress Like everywhere, persons with disabilities in Mozambique face physical, social, economic and/or environmental barriers to participation. For example, 17 percent of persons with disabilities in Mozambique have been refused entry into a school or preschool because of their disability. Prior to its ratification of the International Convention on the Rights of People with Disability (ICCPD), which protects and promotes the rights and dignity of persons with disabilities, Mozambique had already pioneered progressive measures to promote the inclusion of persons with disability through specific principles in the Constitution of the Republic and the development of multisectoral plans on disability. Furthermore, the Mozambican Government proposed a new set of commitments that were presented at the London Summit in July 2018, reaffirming its adherence to the International Convention on the Rights of People with Disability. The Mozambican Minister for Gender, Children and Social Action, Her Excellency Cidália Manuel Chaúque Oliveira, today spoke at an event on 18th December to launch the study, ‘Towards Social, Economic and Inclusive Policies for People with Disability in Mozambique.’ The study is the result of consultations with people with disabilities of different types and other stakeholders working to promote the rights of persons with disabilities (PWDs) in the Nampula, Beira and Maputo regions of Mozambique. The consulations aimed to find out about the socio-economic and political situations of PWDs and the barriers they face, as well as propose solutions to those problems. The consultation is part of the effort to establish a National Agenda for greater social, economic and political inclusion of PWDs in Mozambique. The study identifies the opportunities for, progress made, obstacles to, and consensus on national policies and strategies. It articulates a ways forward for building an inclusive society and achieving social justice. The study contibutes to Mozambique’s efforts work effectively towards national and international commitments to inclusive development. The study was undertaken as part of the Commonwealth Partnership for Democracy (CP4D) programme. It was carried out by WFD Mozambique in partnership with the Mozambican Association of People with Disability (ADEMO), the Mozambican Forum of Associations for People with Disability (FAMOD), and the Assembly of the Republic of Mozambique, in collaboration with the Ministry of Gender, Children and Social Action and with the technical advice of the Centre for Human Rights of the University of Pretoria in South Africa.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; government policy / politica governamental; health / saúde; social inclusion & exclusion / inclusão e exclusão social

Regional Disparities in Fertility Preferences and Demand Satisfied for Family Planning by Modern Methods across Levels of Poverty - Assaf, Shireen; Wang, Wenjuan (USAID, 2019)
Research has highlighted disparities in family planning outcomes by wealth and by region separately. This analysis examines regional disparities within specific poverty groups. Twelve USAID family planning priority countries with recent DHS or AIS surveys were selected for the analysis, including 11 DHS surveys (Democratic Republic of Congo (DRC), Ethiopia, Ghana, Haiti, Malawi, Nepal, Nigeria, Pakistan, Rwanda Uganda, and Zambia) and one AIS survey (Mozambique). The measure of absolute poverty used in the analysis was comparable across the surveys. Households were divided into three groups to define the level of poverty: not extremely poor, extremely poor but not asset poor, and extremely poor and asset poor. Two outcomes were examined for women in union: ideal number of children and demand for family planning satisfied by modern contraceptive methods. The analysis examined regional disparities in these outcomes within each of the three poverty groups using descriptive statistics, maps, and regression analyses. The results showed patterns specific to individual countries. In some countries, including Haiti, Malawi, and Rwanda, few or no regional disparities were apparent. In others, one or a few clustered regions stood out from the rest by having worse outcomes across all poverty groups (for example, Somalia region in Ethiopia). Other countries showed more regional variability in just one of the three poverty groups. This was especially true in several countries for demand for family planning satisfied by modern methods among the extremely poor and asset poor group. These results highlight the need for family planning programs to focus on specific regions where disparities exist, and on poverty groups where little of the demand for family planning is satisfied by modern methods.
Keywords: #Reviews & Framing / Revisões e Organização; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; G - north / norte; Health PEA; L - english / inglês; Northern PEA; demographics / demografia; gender / género; health / saúde; poverty / pobreza

Final Evaluation Report - “Improving oversight in Mozambique's governance” (2016-2019) - FCG International Ltd (FCG International Ltd, 2019)
An external evaluation of the project was conducted in April - May 2019. It looked into the strategy, performance and attainment of the general development goals. The results of the evaluation will be taken into account in the planning of a possible second phase of the project. According to the evaluation, the project is highly relevant both for the strategic partnership between Finland and Mozambique, as well as for the sustainability and inclusiveness of the economic growth arising from the extractive industries and the development of democratic governance. Finnish discretionary government transfers are used to support the Improving Oversight in Mozambique’s Governance 2016–2019 project, which aims to strengthen parliamentary oversight of the management of natural resources in Mozambique. It is a joint project of three organisations; Netherlands Institute for Multiparty Democracy (NIMD), Political Parties of Finland for Democracy (Demo Finland) and Instituto para Democracia Multipartidária from Mozambique (IMD). The project was launched in Mozambique in 2017 and it will be closed at the end of 2019; with a budget of EUR 1,500,000. The evaluation emphasises that strengthening parliamentary oversight is a long-term objective. The project has managed to reach preliminary results in a short time frame in that, for example, Members of Parliament have a better understanding of the challenges met by the extractive industries, and for the first time in Mozambique, there is regular exchange of information and cooperation between national and provincial parliaments. However, performance is not on a sustainable foundation. Sustainable impacts require that a greater number of MPs are trained and the training and research centre of Parliament and the technical secretariats of the provincial parliaments are strengthened. In addition to capacity building, the Parliament should be strengthened by creating wider partnerships and networks with other actors in society. In order to consolidate the results of the project and to improve their sustainability, the evaluation strongly recommends the Ministry for Foreign Affairs to continue the project in cooperation with the new Parliament, which will be elected in October 2019, and with provincial parliaments. It would be useful for the new MPs starting their work at the beginning of 2020 that they make use of the materials produced during the project and consult the MPs who were trained during the project. Additionally, the evaluation recommends the Ministry for Foreign Affairs to continue the project with the same partners, because they have managed to establish well-functioning and confidential relations with the Parliament and other political actors.
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; M - evaluation / avaliação; citizenship & participation / cidadania e participação; decentralization / descentralização; governance / governação

Input subsidies in Mozambique: The future of peasant farmers and their seed systems - Lewis, Linzi (African Centre for Biodiversity, 2019)
In this paper, we discuss and assess the input subsidy programmes in Mozambique, as part of the larger agriculture policy landscape, the impact this has had on the agricultural sector in Mozambique, and particularly on smallholder farmers. Input subsidy programmes in Mozambique are fragmented and operate more along the lines of projects and pilots. Therefore, this paper selects a few key projects to explore approaches being taken by the Mozambican government, along with international donors, providing agricultural inputs to peasant farmers. Notably we consider the more recent Food and Agriculture Organization (FAO)’s input subsidy programme, and the World Bank funded Agriculture and Natural Resources Landscape Management (SUSTENTA) programme/project, implemented by the National Sustainable Development Fund2 (FNDS), under the Ministry of Land, Environment and Rural Development (MITADER). This paper provides a brief background to agriculture in Mozambique, followed by the agricultural policies, plans and budgets guiding agricultural investments in the country. After briefly outlining the agricultural sector – notably seed, fertiliser and agro-dealers in the country – we discuss and analyse selected input subsidy programmes in Mozambique. The paper closes with a conclusion and recommendations to feed into future discussions with farmers, farmer organisations, non-governmental organisations (NGOs) and others in Mozambique.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; agriculture / agricultura

Subsídios em insumos em Moçambique: O futuro dos agricultores camponeses e dos seus sistemas de sementes - Lewis, Linzi (African Centre for Biodiversity, 2019)
Neste artigo, discutimos e avaliamos os programas de subsídios em insumos em Moçambique, como parte do panorama mais amplo da política agrícola, o impacto que estes têm tido no sector agrícola em Moçambique e particularmente nos pequenos agricultores. Os programas de subsídios em Moçambique são fragmentados e operam mais ao logo das linhas de projectos e pilotos. Este artigo selecciona, portanto, alguns dos projectos principais para explorar abordagens que estão a ser usadas pelo governo Moçambicano, juntamente com doadores internacionais, para fornecer insumos agrícolas aos produtores camponeses. Notavelmente consideramos o programa de subsídios em insumos mais recente da FAO (Organização para Alimentação e Agricultura), e o projecto/ Programa Agrícola e de Gestão de Paisagens de Recursos Naturais (SUSTENTA) financiado pelo Banco Mundial, implementado pelo Fundo Nacional de Desenvolvimento Sustentável (FNDS), debaixo do Ministério da Terra, Ambiente e Desenvolvimento Rural (MITADER). Este ensaio oferece um breve histórico da agricultura em Moçambique, seguido por políticas, planos e orçamentos agrícolas que guiam os investimentos agrícolas no país. Após brevemente esboçar o sector agrícola – nomeadamente os vendedores de sementes, de fertilizantes e de agroinsumos no país – – discutimos e analisamos programas seleccionados de subsídios em insumos em Moçambique. O artigo encerra com uma conclusão e com recomendações para contribuir para discussões futuras com agricultores, organizações de agricultores, organizações não-governamentais (ONGs) e outros em Moçambique.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; agriculture / agricultura

Additional Financing to the Agriculture and Natural Resources Landscapes Management Project (SUSTENTA) - World Bank (World Bank, 2019)
Proposed Development Objective(s) Parent The project development objective is to integrate rural households into sustainable agriculture and forest-based value chains in the Project area and, in the event of an Eligible Crisis or Emergency, to provide immediate and effective response to said Eligible Crisis or Emergency. Components Agriculture and Forest-Based Value Chain Development Securing Land Tenure Rights and Increasing Natural Resources Resilience Project Coordination and Management Contingency Emergency Response
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; development partners / parceiros de cooperação; governance / governação; land governance / gestão de terra; natural resources / recursos naturais

Limits of gender equality: Poor, uneducated Mozambicans less likely to see improvement - Bhoojedhur, Sadhiska; Isbell, Thomas (AFR Barometer, 2019)
Gender equality is enshrined in Mozambique’s Constitution and promoted through its participation in international conventions and treaties as well as its 2004 Family Code, which requires equality in property and family law, including sharing of assets within marriage (International Federation for Human Rights, 2007; UN Women, 2012). During the launch of a National Plan of Action on Women, Peace, and Security in June 2018, the Minister of Gender, Children, and Social Welfare reiterated the government’s commitment to promoting gender equality, emphasizing that equal participation of men and women in all spheres of society is a prerequisite for sustainable development (AllAfrica, 2018). Yet gender disparities are a persistent reality for many women in Mozambique, in forms ranging from child marriage and teen pregnancy to domestic violence and sexual abuse (Cumbe, Materula, Sadler, & Agosta, 2017; Christensen, 2018). According to a United Nations Country Team report (2013), more than half of Mozambican women report having suffered some form of physical, sexual, or psychological violence, and almost three-fourths of girls said they were aware of cases of sexual abuse and harassment in their schools. Mozambique ranks 138th out of 164 countries on the United Nations Development Programme’s (2018) Gender Development Index, and especially in the North and in rural areas, traditional patriarchal values remain strong (Tvedten, 2011). In leadership roles, Mozambican women are better represented than women in many other African countries: 40% of the Mozambican Parliament are women (World Bank, 2018). However, while the Global Gender Gap Report ranked Mozambique No. 1 in Africa in 2008 in terms of economic participation and opportunity, by 2018 the country had dropped to No. 7 (No. 49 in the world) because of setbacks in women’s labour-force participation, particularly in senior and managerial positions (World Economic Forum, 2008, 2018). According to the latest Afrobarometer survey, a majority of Mozambicans think gender equality has been achieved with regard to education, work, and land, and give the government good marks on promoting opportunities for women. However, poor and lesseducated citizens are considerably less likely to perceive progress on gender equality. Moreover, Mozambicans’ support for equality is uneven: While most endorse equality in access to land and political leadership, majorities prioritize men when it comes to getting a job and say families are better off if a woman, rather than a man, takes care of home and children.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; education / educação; gender / género; poverty / pobreza

IV Recenseamento Geral Da População E Habitação 2017: Resultados Definitivos - INE (Instituto Nacional de Estatística, 2019)
O Instituto Nacional de Estatística (INE) apresenta nesta publicação os resultados definitivos do IV Recenseamento Geral da População e Habitação de 2017 (Censo 2017) referentes a Moçambique. Como é do conhecimento geral, o Censo 2017 tinha por objectivo estabelecer o conhecimento estatístico, quantitativo e qualitativo, tão exacto quanto possível, da população moçambicana e de todos os demais residentes e presentes no território nacional, bem como do parque habitacional (Lei do Recenseamento, n.º 4/79 de 19 de Maio). O Censo 2017 foi realizado em todo o território nacional de 1 a 15 de Agosto de 2017. Os resultados disponibilizados através da presente publicação referem-se a 1 de Agosto desse ano (momento censitário, ou seja, referência temporal à qual a informação recolhida durante o recenseamento é relativa).
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; demographics / demografia

Inquérito Nacional Sobre Indicadores de Malária - IIM (National Malaria Indicator Survey - MIS) 2018 - INS; ICF (INS/Mozambique, INE, PNCM, ICF, 2019)
O presente relatório resume os resultados do Inquérito Nacional sobre Indicadores de Malária em Moçambique, conduzido pelo Instituto Nacional de Saúde (INS), em colaboração com o Programa Nacional de Controlo da Malária (PNCM) e o Instituto Nacional de Estatística (INE). O inquérito contou com a assistência técnica da ICF, através The Demographic and Health Surveys (DHS) Program. O inquérito foi financiado pela Agência dos Estados Unidos para o Desenvolvimento Internacional (USAID) através dos fundos da Iniciativa do Presidente dos Estados Unidos Contra a Malária (PMI) e o Fundo das Nações Unidas para a Infância (UNICEF).
Keywords: G - Mozambique / Moçambique; G - north / norte; Health PEA; L - portuguese / português; M - survey / inquérito; Northern PEA; demographics / demografia; health / saúde

How Does the World Bank Build Citizen Engagement Commitments into Project Design? Results from Pilot Assessments in Mozambique, Myanmar, Nigeria, and Pakistan - Nadelman, Rachel; Sah, Anjali; Le, Ha (IDS, 2019)
How and to what degree is the World Bank putting its new institutional citizen engagement (CE) commitments into practice? This question guides an independent assessment that the Accountability Research Center (ARC) at American University has undertaken as part of the Institute of Development Studies (IDS)-led Action for Empowerment and Accountability (A4EA) research programme’s investigation into how external actors can best support local processes of and conditions for empowerment and accountability. This report investigates the World Bank’s incorporation of CE into project design, the critical early stage of donor engagement. To accomplish this, ARC reviewed the World Bank’s fiscal year 2015–17 investment project portfolios for four A4EA priority countries, Mozambique, Myanmar, Nigeria, and Pakistan, which covers 57 projects that range from US$19 million to US$600 million. The analysis determines whether projects commit to seeking a strategic approach to CE, which involves combining multiple tactics so that the whole could be greater than the sum of the parts. This assessment of CE commitments is intended to help to inform possible national, civil society organisation strategies to monitor whether and how these commitments are actually implemented in practice.
Keywords: G - Mozambique / Moçambique; L - english / inglês; development partners / parceiros de cooperação

Impacto Dos Conflitos Armados Na Vida Das Mulheres e Raparigas Em Moçambique: Relatório Da Pesquisa De Campo Nas Províncias De Nampula, Zambézia, Sofala E Gaza - Lawyers Without Borders (Lowyers Without Borders, 2019)
O presente estudo pretende entender como a violência político-militar no país afectou as mulheres e as raparigas e que medidas foram tomadas de forma a apoiar as mulheres víctimas da violência. O estudo visa trazer à luz os diferentes tipos de violações de direitos humanos e de violência cometidos contra as mulheres e raparigas no contexto dos conflitos armados considerando que, e segundo Moura, Silva et all (2012) “A inexistência de dados, estudos e análises sobre violências (directas) contra mulheres e jovens do sexo feminino na Guiné-Bissau, Angola e em Moçambique, torna difícil a tarefa de traçar com precisão uma tipologia das violências cometidas contra estes grupos, ou aferir a sua evolução no pós-conflito armados”. Em termos de actores, o estudo privilegiou, entre outros aspectos, a análise dos principais perpetradores e as suas motivações, entre outros aspectos como forma de definir o perfil das víctimas do conflito armado usando critérios como a faixa etária, o gênero, grau de escolaridade, estado civil, filhos e perfil social e económico. Por outro lado, e considerando o papel da mulher como um factor importante na sociedade, o estudo analisou igualmente a participação directa ou indirecta das mulheres no conflito armado moçambicano cuja maior tónica incidiu sobre a guerra dos 16 anos. No final, o estudo identificou propostas de medidas de reparação – de carácter individual e colectivo derivados das consequências dos conflitos armados na vida de mulheres e raparigas em Moçambique a partir da escuta das reivindicações das próprias víctimas.
Keywords: G - Mozambique / Moçambique; G - central / centro; G - north / norte; G - south / sul; GP - Gaza; GP - Nampula; GP - Sofala; GP - Zambézia; L - portuguese / português; conflict / conflito; gender / género

Hiring of Foreigners in Mozambique - Regulatory Regimes and Practices - JICA (Agency for Promotion of Investment and Exports (APIEX), 2019)
The laws and regulations for hiring foreign nationals have been enacted with the aim of protecting the national workforce, ensuring the availability of jobs for them, while limiting employment of foreigners to those positions with levels of technical and professional skills and qualifications which are either nonexistent or insufficient in the country. Historically, the main instrument used by the Mozambican Government to achieve foreign investment promotion balanced with national employment, was the hiring of foreign employees through the quota mechanism, which is still in use at present. In the present context, it is fundamental that the regime of hiring foreign labour allows for certain flexibility but at the same time does not compromise the structural principle of protecting the local labour force. This document is prepared to provide the current regulatory framework for hiring of foreign nationals, as a reference mainly for foreign investors considering employing foreigners in their projects in Mozambique.
Keywords: G - Mozambique / Moçambique; L - english / inglês; employment / emprego

The State of ICT in Mozambique 2018 - Gillwald, Alison; Mothobi, Onkokame; Rademan, Broc (RIA Policy Paper, 2019)
Mozambique has a challenging path ahead if it is to realise the full potential of the ICT sector in developing its economy and to make progress on the information communication technology targets that are intended as enabling the achievement of the United Nations’ Sustainable Development Goals. Mozambique’s successes include licensing and regulatory achievements in telecommunications, which have stimulated competition and contributed to meeting national policy objectives.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; access to services / acesso a serviços; gender / género; infrastructure - energy / infrastrutura - energia; infrastructure / infrastrutura

Social Cohesion Indicators Bank: illustrative indicators to measure changes in social cohesion - Catholic Relief Services (Catholic Relief Services, 2019)
WHAT IS SOCIAL COHESION? Social cohesion is a concept with various interpretations.2 Some definitions emphasize social harmony and inclusion, human solidarity in diversity, and the inclusive wellbeing of a community or society. Others focus on the social fabric: the abundance of connections and associations in a society, and the presence of linkages and counterbalances that shape the relationship between citizen and the state. CRS views social cohesion as the strength, quality and diversity of relationships between and among individuals, groups and communities, coupled with linkages between society and the state, markets and other institutions, all based on trust, respect, mutuality and equal opportunity, for the dignity and wellbeing of every person and the common good of all.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; M - indicators / indicadores; Northern PEA; society / sociedade

Conflict at a Crossroads: Northern Mozambique at a Crossroads - Devermont, Judd; Columbo, Emilia (Northern Mozambique at a Crossroads, 2019)
On October 5, 2017, a group of armed men attacked three police stations in Moçimboa da Praia, starting nearly two years of violence and insecurity that still show no sign of ending. Between the first October incident and August 27, 2019, extremists conducted 173 attacks—79 percent of which were committed against civilians—resulting in over 350 deaths, according to the Armed Conflict Location and Event Database (ACLED).1 There is no consensus on the name or construct of the group committing the violence, but for the purposes of this paper, we will refer to the group as Ahlu Sunnah Wa-Jama (ASWJ), which is one of the several names that observers and local communities have ascribed to the militants.2
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict / conflito; youth / juventude

Independent Report of the Extractive Industries Transparency Initiative - EITI (Extractive Industries Transparency Initiative (EITI), 2019)
This is the ninth report reconciling payments made by companies operating in the extractive industry and receipts from the State. 97% of tax revenues from the extractive industry were reconciled. The differences between the payments by the companies and the receipts from the State correspond to 0,17% of the amounts confirmed by the State in 2019
Keywords: *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; extractive industries / indústrias extractivas; natural resources / recursos naturais

Anuário Estatístico - Statistical Yearbook 2018 - Moçambique - INE (Instituto Nacional de Estatística (INE), 2019)
À semelhança das edições anteriores, o Anuário Estatístico 2018 contém informações que permitem traçar um perfil sintético da realidade sócio-económica de Moçambique em seus múltiplos domínios.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; demographics / demografia

IV Recenseamento geral da população e habitação 2017: resultados definitivos Moçambique - Instituto Nacional de Estatística (INE) (Instituto Nacional de Estatística, Governo de Moçambique, 2019)
O Instituto Nacional de Estatística (INE) apresenta nesta publicação os resultados definitivos do IV Recenseamento Geral da População e Habitação de 2017 (Censo 2017) referentes a Moçambique. Esta publicação encontra-se estruturada em duas partes: • A primeira inclui principais conceitos e definições necessári os para a interpretação dos resultados; • A segunda é composta por quadros que foram definidos como prioritários para as publicações em suporte de papel.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; demographics / demografia

The Health Budget: The Disparity Between Political Discourse and Practice - N'weti (N'weti, 2019)
Key Messages: - Health is a human right and is constitutionally protected in Mozambique; - The health sector is considered a priority sector by the Government of Mozambique; - The health sector is amongst the least funded by the State Budget in the past four years, (with less than 8% on average), against the 15% assumed in Abuja; - For the year 2014, of the 762.8 million USD allocated to the health sector, 44% came from external sources (REO MOH, 2014). The combined PROSAUDE resources, and the speci c "off-budget" projects’ funding demonstrates the enormous reliance on external partners to support the country’s health strategy; - There is an urgent need to increase internal State Budget funding for the health sector to ensure sustainability.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; access to services / acesso a serviços; budget / orçamento; health / saúde

Relatório De Diagnóstico Sobre Transparência, Governação E Corrupção - República de Moçambique (International Monetary Fund (IMF), 2019)
A economia de Moçambique encontra-se num ponto de viragem, e os esforços para abordar as vulnerabilidades em matéria de governação e corrupção podem ter um impacto positivo duradouro. Já tomámos medidas para abordar as vulnerabilidades em matéria de governação e corrupção. Contudo, reconhecemos que subsistem falhas em diversas áreas relevantes da economia. A fim de abordar algumas das debilidades restantes, temos reformas de governação em curso e em perspectiva em várias áreas, muitas delas apoiadas por diversos doadores. Reconhecemos que a implementação eficaz continua a suscitar preocupações. Reconhecemos que a falta de transparência pode igualmente exacerbar as preocupações com a governação e agravar o risco de conflitos de interesse. Embora reconheçamos que temos um papel essencial a cumprir na melhoria da governação e no combate à corrupção, não podemos fazê-lo sozinhos. Estamos preparados e dispostos a tomar medidas concretas.
Keywords: G - Mozambique / Moçambique; L - portuguese / português; accountability / responsabilização; corruption / corrupção; transparency / transparência

Impacto das Uniões Prematuras na Educação, Saúde e Nutrição em Moçambique: Resumo do Documento - ROSC (ROSC - F;orum da Sociedade Civil para os Direitos da Criança, 2019)
As uniões prematuras constituem um dos principais problemas sociais na África Austral que, pelas suas consequências negativas em cadeia: gravidez precoce,desnutrição crónica,fístula obstétrica,abandono escolar,se tornam um problema igualmente económico, uma barreira ao desenvolvimento socioeconómico. No caso de Moçambique, o problema afecta cerca de metade das raparigas com menos de 18 anos, o que faz do país um dos cinco mais afectados a nível da Comunidade dos Países da África Austral (SADC). Para fazer face a este problema, várias acções têm sido levadas a cabo, entre campanhas de sensibilização, programas de resgate de meninas em situação de vida marital precoce, lobby e advocacia para o fortalecimento do quadro institucional e legal, bem como estudos para melhor informar as acções referidas. No entanto, quase todas as pesquisas feitas à volta das uniões prematuras têm sido na perspectiva sociológica ou antropológica. Por isso, o Fórum da Sociedade Civil para os Direitos da Criança (ROSC), no âmbito das acções da Coligação para a Eliminação dos Casamentos Prematuros (CECAP), com o apoio da OXFAM, através do Programa AGIR, decidiu realizar este estudo de perspectiva económica, para aferir o impacto que as uniões prematuras têm na educação, saúde e nutrição no país. Este estudo foi elaborado com quatro finalidades: primeira, contribuir para o debate sobre o impacto das uniões prematuras; segunda, elucidar aos actores-chave sobre as consequências das uniões prematuras para o desenvolvimento do país; terceira, despertar a consciência dos tomadores de decisão e da sociedade no geral sobre os impactos negativos das uniões prematuras na educação, saúde e nutrição; quarta e última finalidade, contribuir para despertar a atenção para a necessidade do desenho de programas, políticas e leis que visam mitigar os impactos negativos das uniões prematuras
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; education / educação; gender / género; health / saúde

Representação Comunitária na Gestão de Terras e Recursos Naturais. Nota Técnica - Salomão, Alda; Mário, T. V.; Tanner, Christopher (SPEED+; USAID, 2019)
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; agriculture / agricultura

Informe Orçamental: Acção Social - Moçambique 2019 - UNICEF (UNICEF, 2019)
Em 2019, pela primeira vez na história documentada, dois fortes ciclones tropicais atingiram Moçambique na mesma estação do ano. No dia 14 de Março, o ciclone tropical IDAI atingiu o porto de Beira (afectando 50 distritos em 5 províncias ), e seis semanas mais tarde, o ciclone Kenneth atingiu o norte de Moçambique (afectando 14 distritos em duas províncias). A devastação causada pelos ciclones poderá elevar o número de crianças que necessitam urgentemente de assistência humanitária nas áreas afectadas – em termos de cuidados de saúde, nutrição, protecção, educação, água e saneamento - para aproximadamente 1.5 milhões, em Moçambique. No Orçamento do Estado de 2019, foram alocados ao Sector de Acção Social - compreendido na sua definição restrita como o sector gerido pelo Ministério do Género, Criança e Acção Social (MGCAS) e o Instituto Nacional de Acção Social (INAS) - 6.9 mil milhões de Meticais (mm), o que representa a maior dotação de todos os tempos, tanto em termos nominais quanto reais. O orçamento do sector da Acção Social de 2019 absorve uma participação de 2% de todo o Orçamento do Estado e de 0.7% do Produto Interno Bruto previsto. Apesar do aumento da verba à Acção Social, Moçambique não está em vias de atingir o objectivo da Estratégia Nacional de Segurança Social Básica (ENSSB) de alocar 2.23% do PIB ao sector até 2024. Em termos nominais, os recursos internos alocados à Acção Social no Orçamento de 2019 equivalem a 4.6 mil milhões de Meticais (mm), o que representa um aumento de 7% em relação a 2018. Em termos proporcionais, a relação entre os recursos internos e externos é de 67 a 33 por cento, em 2019. Porém, o maior investimento externo é o crédito do Banco Mundial ao Programa de Assistência Social Directa (PASP); embora isto seja identificado como recursos externos no Orçamento do Estado, o programa PASP é de facto integralmente financiado a nível interno, uma vez que o Governo Moçambicano terá que pagar o empréstimo e os juros correspondentes. A significativa auto-suficiência do sector de Protecção Social indica o compromisso do Governo relativamente ao sector, bem como a sustentabilidade e a apropriação dos programas dos sectores que não dependem de financiamento externo e do propósito dos doadores. Mais de 90 por cento do orçamento do sector foi afectado ao INAS, dos quais a maior parte foi direccionada para as suas delegações, o que é equiparável à participação do ano anterior. Os gastos com o sector da Acção Social são efectivamente bastante descentralizados: a relação entre os recursos centrais e não centrais é de 13 a 87 por cento em 2019. Os programas de protecção social receberam um total de 5.4 mil milhões de Meticais no orçamento de 2019. Isto corresponde a 78 por cento do orçamento do Sector da Acção Social, 1.6 por cento do Orçamento Geral do Estado e 0.5 por cento do PIB. Em 2019, os programas do INAS visaram 609.405 agregados familiares beneficiários. Isto representa um aumento de 7 por cento em relação aos 567.290 agregados familiares beneficiários visados em 2018. Embora a meta de 2019 aumente a cobertura de Protecção Social para aproximadamente 22 por cento dos agregados familiares pobres e vulneráveis, é pouco provável que a meta de 25 por cento do Programa Quinquenal do Governo (PQG) seja cumprida até o final do ano. As dotações per capita para os pobres aumentaram em relação aos anos anteriores, mas ainda não são equitativas em todo o país, o que é motivo de preocupação no actual contexto de espaço orçamental limitado e aumento das desigualdades. Com efeito, embora tenham sido envidados esforços para melhorar o direccionamento dos programas de Protecção Social, as províncias de Niassa, Zambézia e Nampula - que recebem as maiores dotações nominais - recebem a verba mais baixa “porpobre” (i.e., dotação por pessoa considerando apenas pessoas que vivem abaixo do nível nacional definido de pobreza).
Keywords: *tagged; G - Mozambique / Moçambique; L - portuguese / português; budget / orçamento; social action / ação social; social protection / proteção social

State Budget Proposal for Fiscal Year 2019 – Mozambique, Analysis of the Social and Economic Sectors - UNICEF (UNICEF Mozambique, 2019)
Key messages: 1. The envelope of resources for the 2019 State Budget is set to increase to MT 340 billion (from MT 303 billion in 2018), representing Mozambique’s largest nominal budget; however, once factoring in the depreciated currency and high inflation of recent years as well as high debt servicing payments, the purchasing power of this envelope –including for priority sectors– no longer represents a historical high. 2. The share of resources dedicated to investment in Mozambique has been steadily declining, particularly since 2015, due to frozen donor support and a crowding out effect by proportional increases in financial operations and recurrent spending. While in the 2019 Budget Proposal investment has increased to a 30 percent share of total spending, it is still far below the 40 percent norm registered a decade ago. 3. Over the past decade, the share of resources dedicated to the district level has increased at the expense of resources directed to the provincial level; meanwhile central-level expenditure has remained unchanged. In the 2019 Budget Proposal, the central level will, as usual, receive the most resources (64 percent), followed by districts (19 percent), provinces (15 percent), and then municipalities (2 percent). 4. Relative to the Government’s Five Year Plan (PQG), “Priority II: Develop Human and Social Capital” (i.e. priority economic and social sectors) is expected to receive the largest share of funding in the 2019 Budget Proposal. 5. The government has set the goal of allocating at least 60 percent of resources to the priority sectors (according to its methodology of excluding financial operations and debt servicing from the denominator); however, because financial operations and debt servicing have soared as a share of total spending, their 60 percent is no longer a reliable benchmark (e.g. priority sector allocations grew 3.5 times in nominal terms from 2009 to 2019 while the entire budget grew 4 times over the same period) . Proportional priority sector spending as a share of the entire budget (including financial operations and debt servicing) has dropped significantly in recent years. In the 2019 Budget Proposal, it is projected at 51 percent of the entire budget. 6. Among Priority Economic and Social Sectors, Water & Public Works, Transport & Communications, and Agriculture & Rural Development more than doubled their proposed allocations for 2019 relative to 2018 initial allocations. The Education, Health, and Social Action Sectors are also expected to receive a larger allocation than in 2018, but the increase will be smaller. The Infrastructure Sector (mainly the roads sub-sector) will be the only one experiencing a cut in allocation relative to the 2018 Budget.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; budget / orçamento